ULASAN KEPUSTAKAAN SISTEMATIS: PEMBENTUKAN KARAKTER PERAWATAN SOSIAL PADA SISWA SEKOLAH DASAR - Nailisshifa, Wardania Nur; Mutiara, Ayu; Rikza, Muhamad Dafa Zakhi; Fitriani, Rohmah Indri; Setiawaty, Rani (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Character is the values that a person has that are formed through interaction with his or her environment. These interactions shape a person's attitudes and behaviors, which ultimately shape his personality. This research focuses on the learning mechanism of social care character, what factors affect the character of social care in students, and its effects. Data analysis involves subtracting, presenting, and drawing conclusions from data. The purpose of this study is to describe the formation of social care character in elementary school students. This study uses Systematic Literature Review (SLR) to examine in depth various journal articles related to efforts to build social care characters through learning in elementary schools. The data of this study are articles from 22 journals collected from "Google Scholar" with the keywords "character building", "Social Care", "elementary school". Furthermore, the data is analyzed in depth to draw a conclusion. Based on the results of the study, it shows that learning strategies that are integrated with moral and social values are carried out through exemplary strategies to foster the character of social care in elementary school students. This approach must be carried out in a sustainable manner and involve various parties in the educational environment.